IRF-5 Is a Mediator of the Death Receptor-induced Apoptotic Signaling Pathway - Hu, Guodong; Barnes, Betsy J. (The Journal of biological chemistry, 2009)
The efficient and regulated response to cellular stress is coordinated by a genetic regulatory network in which a given transcription factor controls the expression of diverse target genes depending on the cell type and/or nature of the stimuli. The tumor suppressor p53 is thought to preferentially regulate the balance between cell survival and death. The interferon regulatory factor 5 (IRF-5), known to be involved in the innate immune response to pathogens, is also a critical regulator of DNA damage-induced apoptosis. Here, we provide direct evidence that IRF-5 promotes apoptosis upon signaling through tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) death receptors (DR). We report that IRF-5 sensitizes tumor cells to TRAIL-induced apoptosis and cell death that is further enhanced by type I interferons. Cells deficient of IRF-5 gave a significantly diminished response to these agents. IRF-5 is involved in DR signaling upstream of caspase 8, in part because of an IRF-5-dependent increase in caspase 8 activation. We provide evidence that TRAIL induces a signaling cascade that leads to the phosphorylation and nuclear localization of IRF-5, resulting in transactivation of key DR signaling components. The results presented here identify IRF-5 as a new mediator of DR signaling and provides molecular insight into the mechanism of TRAIL-induced IRF-5 signaling.